Tourism impact analysis - an inter-sectoral analysis of the Malaysian economy - Abdul Rashid, Zakariah; Abdul Rahman, Abdul Aziz; Othman, Mohd Shahwahid; Suib, Ahmad (Penerbit Universiti Kebangsaan Malaysia, 1993)
Using nation-wide data on tourist expenditures collected by questionnaire method in 1991, the private consumption expenditure and export columns of the 1983 input-output table were broken down into tourist and non-tourist components. The tourist expenditures (local and foreign) were then used to evaluate their impact on each of the sectoral output, employment, commodity taxes and non-competitive imports. The results highlighted a number of tourism strategic sectors and at the same time focus on other sectors which benefit from tourist expenditure through indirect and induced income and employment generations.